Training intensity influences leptin and thyroid hormones in highly trained rowers - Simsch, C.; Lormes, W.; Petersen, K. G.; Baur, S.; Liu, Y.; Hackney, A. C.; Lehmann, M.; Steinacker, J. M. (International Journal of Sports Medicine, 2002)
Leptin (L) is associated with body-weight-regulating and adipostatic functions. Its receptors also may be found centrally. Thyroid hormones regulate metabolic processes mainly by binding at peripheral receptors. Aim of this study was to show if there is a link between those central and peripher regulation systems and to investigate the influence of different training intensities on L and the hypothalamic-thyroid-axis (HTA) in highly trained rowers. Six rowers (18.9 +/- 2.6 y; BMI 22.8 +/- 2.1 kg/m (2)) undertook high intensity resistance training (RT) for three weeks followed by three weeks of endurance training (ET). After each training cycle the subjects had one week for recovery (R1, R2). Blood samples were taken before and at the end of RT, R1, ET and R2. L, thyroid stimulating hormone (TSH), free T3 (fT3) and free T4 (fT4) were measured. After RT, a significant reduction in L, TSH and fT3 was found (p < 0.05). fT4 was unchanged. L remained decreased until the end of R1. After ET, a significant increase of TSH was found. L correlated to basal TSH levels (r = 0.49, p = 0.006) during R. BMI and body fat were unchanged throughout the study and were not correlated with hormonal levels. We speculate a high energy flux during intensified training (RT) caused the decrease of L and the HTA, independent of BMI or body fat. Thus, we conclude a depression of L and HTA is associated with training intensity.